2019
DOI: 10.3390/toxins11040208
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Combinations Prevent Serotype A and Serotype B Inhalational Botulism in a Guinea Pig Model

Abstract: Botulinum neurotoxins (BoNT) are some of the most toxic proteins known, with a human LD50 of ~1 ng/kg. Equine antitoxin has a half-life in circulation of less than 1 day and is limited to a treatment rather than a prevention indication. The development of monoclonal antibodies (mAbs) may represent an alternative therapeutic option that can be produced at high quantities and of high quality and with half-lives of >10 days. Two different three mAb combinations are being developed that specifically neutralize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 57 publications
7
36
0
Order By: Relevance
“…In the present study, all mAbs in each of the four drug products were detected up to 72 days after infusion. Similarly, PK results in a guinea pig model demonstrated that after IV injection, mAb concentrations were able to show protection in a mouse neutralization assay up to 14 days post injection [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all mAbs in each of the four drug products were detected up to 72 days after infusion. Similarly, PK results in a guinea pig model demonstrated that after IV injection, mAb concentrations were able to show protection in a mouse neutralization assay up to 14 days post injection [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the oligoclonal recombinant antibody antitoxins reduced the mortality in mice when administered prior to BoNT challenge [17,33,34,35,36], and post-challenge in mice [37]. Finally, NTM-1631 and NTM-1632 have been shown to protect guinea pigs from challenge with inhaled BoNT when the antibodies were administered prior to challenge [32].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the combination of 3 mAbs against BoNT/A or BoNT/B were found effective in preventing botulism after an aerosol challenge with BoNT/A1 or BoNT/B1. Those mAbs combinations represent an alternative to vaccination in those at risk of BoNT exposure [75].…”
Section: Generation Of Mouse Sheep or Humanized Monoclonal Antibomentioning
confidence: 99%
“…Here we tested a potent human immunoglobulin (IgG) monoclonal antibody (mAb)based drug product, G03-52-01, composed of six co-formulated IgG mAbs that bind to non-overlapping epitopes of BoNT/A [15] and BoNT/B [37,38]. The BoNT/A and BoNT/B antitoxins comprising G03-52-01 (NTM-1631 and NTM-1632) have both completed Phase 1 testing in humans without serious adverse events [39] and unpublished results.…”
Section: Introductionmentioning
confidence: 99%
“…The BoNT/A and BoNT/B antitoxins comprising G03-52-01 (NTM-1631 and NTM-1632) have both completed Phase 1 testing in humans without serious adverse events [39] and unpublished results. These drugs are an equimolar combination of three antibodies and have also been shown to be efficacious in inhalational botulism models in guinea pigs [38]. To determine the ability of BoNT/A and BoNT/B mAb cocktails when used in combination as an alternative to vaccination for the prevention of inhalational botulism, we evaluated the ability of G03-52-01 administered by the intravenous (IV) or intramuscular (IM) route, using an aerosol delivery model in guinea pigs.…”
Section: Introductionmentioning
confidence: 99%